Harmoni Client Centered Therapy Dalam Bimbingan Konseling Kelompok Dengan Al-Qur’an Surat Ar-Ra‘d Ayat 11 - Lalis, Lalis; Maskhur, Maskhur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This article aims to analyse the concept of Client Centered Therapy as one of the group guidance and counselling techniques in the perspective of the Qur'an surah Ar-Ra'd verse 11. More specifically, analyses on this article focus on how the Client Centred Therapy theory views humans, the purpose and techniques of therapy, as well as the relationship between the counsellor and the counselee. This article is based on descriptive-qualitative research. Data are obtained through triangulation techniques, which are then analysed interactively. The results show that the service techniques of guidance and group counselling, with reference to the Client Centered Therapy theory, are in line with the Qur'an surat Ar-Ra'd verse 11. Client Centered Therapy theory and the Qur'an surah Ar-Ra'd verse 11 similarly view that the service techniques of guidance and group counselling contain the meanings of giving opportunities, roles, and, at the same time, respecting the counselee as an active, potential, and empowered person in determining the direction towards his/her personal kindness.